FACTORS ASSOCIATED WITH WAITING TIME FOR ADMISSION OF PATIENTS TO THE ADULT EMERGENCY DEPARTMENT OF A TERTIARY HOSPITAL: Factors associated with waiting time for admission of patients to the adult emergency department of a tertiary hospital - Peña-Capcha, José (2023)
Objective: To determine the waiting time for admission (WTA) of patients to the adult emergency department (ED) of a tertiary hospital and to identify the factors associated with their delay. Methodology: Observational cross-sectional study that included patients older than 14 years admitted during four consecutive weeks (June 2018). We evaluated waiting time from triage to emergency discharge, time between first medical attention, indication for admission to the hospital ward and its completion; the reason for delay, age, sex, priority of care, destination area and admission diagnosis were evaluated. For statistical analysis, Mann Whitney U and Chi-square tests were applied according to type of data, using SPSS-IBM 25.0. Results: 380 patients were included, 51% female, median age 69 years (Inter quartile range 18.7), most frequent reasons for admission were respiratory infection 18% and encephalopathy 10%. The WTA was 9.2 hours (between 0.67 and 112.9) being higher in priority 1 patients, who had retriage or had indication for hospitalization in critical areas. The time between triage and completed admission was 12 hours, being longer for critical areas. The reason for delay for admission was unavailable stretchers in 92.6% because the service was fully occupied. Conclusions: Patients hospitalized in the ED have very long waiting times for admission, with associated factors being lack of availability of stretchers in the ED or indication to enter critical areas.